Strategic Management of Indonesian Navy Regional Comand III Patrol Ship Unit In Supporting Maritime Security Operations - Sutrisno, Sutrisno; Baharudin Anwar; Gunawan Tri utomo (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to identify the actual condition of the management of Satrol Kodaeral III in supporting Maritime Security Operations, identify the factors that are the strengths, weaknesses, opportunities, and threats in the management strategy of Satrol Kodaeral III, and determine the appropriate policies, strategies and efforts in the management of Satrol Kodaeral III in order to increase the effectiveness of maritime security operations. This study uses a mixed method, which combines qualitative and quantitative methods. The unit of analysis used is the individual personnel of the Indonesian Navy within Satrol Kodaeral III. The research instruments used are interviews, questionnaires, and observations. The results of the study found that the management of Satrol Kodaeral III currently still faces various challenges related to limited resources, both in terms of personnel, defense equipment, budget, and existing management systems. However, there are great opportunities to improve operational effectiveness and efficiency through the application of modern technology and integrated strategies. This study contributes theoretically in enriching strategic management studies, especially in the management of the Indonesian Navy organization, by applying SWOT analysis at the operational unit level. This research contributes practically in providing alternative strategies that can be directly implemented in the management of Satrol Kodaeral III to increase the effectiveness of maritime security operations as well as input for the Indonesian Navy leadership in improving the systems, procedures, and management patterns of defense equipment, personnel, and logistics, so that the unit's performance in carrying out its main tasks is more optimal.